Machine Learning with Scikit-Learn Quick Start Guide : Classification, Regression, and Clustering Techniques in Python. - Jolly, Kevin (Packt Publishing Ltd, 2018)
Scikit-learn is a robust machine learning library for the Python programming language. It provides a set of supervised and unsupervised learning algorithms. This book is the easiest way to learn how to deploy, optimize and evaluate all the important machine learning algorithms that scikit-learn provides.